Influences of Interactions with Health and Social Care Systems Following the Experience of Traumatic Brain Injury (TBI) on Residential Instability - Banimahdi, Ramin (Université d'Ottawa / University of Ottawa, 2026)
Background: Traumatic brain injury (TBI) is a leading cause of death and disability around the world. Post-TBI, individuals might experience cognitive, emotional, behavioural, physical, and psychosocial problems. These neurologically driven changes can hinder an individual's ability to gain and sustain employment, lead to income loss, and might influence individuals' ability to maintain their stable housing, leading to residential instability and an increased risk of homelessness. To address their health and housing needs, individuals with TBI benefit from long-term interactions with health and social care systems. Despite these interactions, many individuals go on to experience housing instability and homelessness. Purpose and Objectives: The overall purpose of this research was to better understand how the interactions of individuals with TBI with health and social care systems influence their housing stability. The specific objectives were: 1) to identify the challenges experienced by the homeless or unstably housed population related to TBI, along with the recommendations for addressing them; 2) to better understand the personal experiences of individuals with TBI regarding their interactions with health and social care systems and how these interactions influenced their residential stability; and 3) to describe how a non-profit organization providing community services to individuals with TBI addresses housing needs, prevents homelessness, and supports stable tenancy. Methods: To meet my first objective, I conducted a scoping review in accordance with the Joanna Briggs Institute (JBI) methodology to understand how TBI influences the experiences of individuals who are homeless or unstably housed. For my second objective, I conducted a qualitative narrative inquiry through interviews with individuals with TBI who experienced residential instability following their trauma, to better understand how they navigated their interactions with health and social care systems and their experiences of residential instability. Finally, for the third objective, I conducted a qualitative single case study of a non-profit organization providing community services to individuals with TBI to describe how they guide these individuals toward their services to prevent homelessness and support stable tenancy. The sources of data were semi-structured interviews and agency documentation. Results: Study 1, the scoping review showed that TBI influences various aspects of life in the homeless population, including health, social lives, daily activities, and service utilization. To address these challenges, the included studies recommended routine TBI screenings in homeless care facilities and improved access to neuro-specific rehabilitation. Healthcare settings must also be aware of the housing conditions of their patients with TBI and make appropriate referrals in cases of homelessness or unstable housing to prevent future episodes of homelessness in this population. Additionally, increasing awareness of TBI and its impacts, providing clinicians with training on how to manage clients with aggressive behaviours, and developing policies, strategies, and interventions that address the combined effects of TBI and homelessness are recommended. Study 2, the narrative inquiry, demonstrated the broad impacts of TBI on individuals' lives, including health outcomes, loss of jobs, and loss of social networks. Moreover, the important roles of individuals' socioeconomic status (SES) and the impact of pre- and post-TBI relationships and family dynamics on health and housing outcomes following the TBI were highlighted. Individuals' experiences reflected a lack of knowledge among the healthcare and social service providers about their unique needs and challenges. As well, it showed several gaps in the system related to serving these individuals, including inaccurate assessments, long waitlists for health and housing services, and a lack of providers in the healthcare system. Finally, study 3, the qualitative single case study, showed that the case, an organization that provides community services to individuals living with TBI, inquires about the housing of their clients on initial contacts and then again annually. Apart from their limited supportive housing program with a long waitlist, it also provides some individualized support tailored to the client's needs. However, housing needs are not always successfully met, with limitations in the capacity to provide residential services, infrequent documentation of clients' housing status as an ongoing concern, treating housing as a secondary concern compared with other program areas, and systemic barriers contribute to this process. These systemic barriers limit service capacity and the access of individuals with TBI to this organization. Examples include limited awareness about TBI community services among health and social service providers, inadequate funding and resources, lengthy and complex application processes for housing supports, and excessive formalities and bureaucratic obstacles for implementation of community service plans targeting the housing of individuals with TBI. Conclusion: There is a need to change system-level beliefs about housing for individuals with TBI and to reframe housing in the health and social care systems as a fundamental determinant of health and a basic human right for this population. Healthcare and social service providers should routinely assess and monitor the housing needs of this population, take action within their capacity when instability is identified, and connect clients to appropriate community resources. Sustained government investment in social housing and improvements to income assistance programs that reflect the actual cost of living are also essential. Governments and institutions must recognize and act upon their shared responsibility to prevent homelessness among individuals with TBI.
Keywords: traumatic brain injury; residential instability; healthcare; social services